Physiotherapy assessment of the impact on quality of life after surgical treatment of breast cancer - Zegarski, Wojciech; Basałygo, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2010)
Breast cancer is one of the most frequent malignant neoplasms in women in Poland. There are 10 000 new cases of breast cancer observed every year. The main radical therapy of breast cancer is surgery. The most frequent operative methods are: breast amputation, modified radical amputation and radical breast amputation by means of Halsted method. The majority of problems are associated with lymphoedema of upper limb and mobility limitation of shoulder girdle on the operated side. Breast amputation was followed by different degrees of deterioration of the quality of life for the majority of patients. At this paper carrying out impact physiotherapy effects on quality of life including the most frequent operative methods. The investigations were carried out in 40 women. The examinations included: measurements of the upper limbs circumference, measurements of the mobility range in shoulder girdle and QLQ-BR23 questionnaire to exam the quality of life. The aim of research was evaluate effect of therapeutic rehabilitation of patients after the surgery treatment on quality of life. For this purpose examined to estimation the quality of life in the 1,2 and 3 months after the operation, and estimation the impact of individual factors of rehabilitation on quality of life. All women enrolled participated in the study, regularly, do exercise at home according to the specific scheme. The women with lymphoedema also massaged the manual lymph drainage. It showed a considerable impact physiotherapy effects on quality of life. Increase in mobility range in acromial joint and reduction lymphoedema caused increase quality of life.